Seed Heteromorphism and Effects of Light and Abiotic Stress on Germination of a Typical Annual Halophyte Salsola ferganica in Cold Desert - Ma, Yali; Wang, Juan; Zhang, Jinghua; Zhang, Shiyue; Liu, Yanxia; Lan, Haiyan (Frontiers in Plant Science, 2018)
Seed heteromorphism is a common characteristic of halophyte and an adaptation to the spatial and temporal variations of natural habitats. Differences in dormancy and germination requirements have been documented in heteromorphic seeds of many species, but the mechanisms for maintenance between different status in various populations have not been well-understood. Salsola ferganica is a typical annual halophyte in Chenopodiaceae distributed in cold desert, in the present study, we found that it could produce three distinct types of seed according to the shape and size of winged perianth (WP), which differed in dispersal ability, dormancy and germination behaviors. Our further investigation revealed that light could significantly promote germination of heteromorphic seeds of S. ferganica, and WP inhibited while GA3 enhanced germination, which suggests that S. ferganica seeds possessed a photo-sensitive combined with morphological and non-deep physiological dormancy type, in which light was the dominant factor. Not like other desert plant species, the germinability of heteromorphic seeds of S. ferganica could not sustain for long (only 1-3 years), especially the small seeds, and was affected by storage time, temperature, salinity, etc., even the environmental conditions of the maternal plant. Thus, the differences of characteristics existed among heteromorphic seeds and variations of heteromorph ratio among different calendar years were presumed as diverse adaptation strategies integrated in the individual mother plant, and might apply important ecological significance for successful reproduction of the species in the unpredictable cold desert.